Determinan Loyalitas Pelanggan Toko Gramedia Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Sri Murtiasih; Denia Nabilah Putri (ARBITRASE: Journal of Economics and Accounting, 2024)
Retail stores are constantly trying to improve store atmosphere, service quality, and product diversity in order to survive and grow in this era of increasingly fierce competition. The aim of this research is to determine the influence of store atmosphere, service quality, and product diversity on customer loyalty through customer satisfaction as an intervening variable at Gramedia stores in Bogor City. The analysis method for this research uses quantitative methods with primary data sources obtained through distributing questionnaires via google form with a sample of 150 respondents for validity, reliability, normality test, multicollinearity test, heteroscedasticity test, t test, R2 coefficient of determination test, and sobel test. Data processing in this study used the SPSS version 25 application. The results of this study indicate that the variables of store atmosphere, service quality, and product diversity affect customer satisfaction. Service quality and product diversity affect loyalty, while store atmosphere has no effect on customer loyalty. Customer satisfaction affects customer loyalty. Store atmosphere, service quality, and product diversity affect customer loyalty through customer satisfaction as an intervening variable at Gramedia stores in Bogor City.